Paradoxes of Rationalistic Ethics Versus Apparent Paradoxes of Irrational‑Religious Ethics in Kierkegaard’s Philosophy - Чизмар, Валентина (Sabornost - The Theological Year-book, 2016)
The author in this paper considers Kierkegaard’s ethics, derived from irrational aspects of faith, arguing that irrational‑religious orientation can provide legitimacy to ethics as a science, while at the same time overturn the paradox which is attributed to such ethics. In this endeavor, author points to the weakness of rational ethics and clarifies the keys of paradoxes and problems of ethics, which particularly visible in the negation of individual existence and inability of ethics to carry out genuine moral rebirth of man. Disadvantages of the rational ethics are particularly visible in the modern world without spirit, but also in objective, rational approach which creating the moral formalism and does not know how to support individuals in its key existential situations, how as for example Kierkegaard proves in the Abraham’s and Job’s life stories. Truly ethics should be taken care about the individual (not common man), and its basis is need to be spiritual love, which is based primarily on the love relationship of man to God, continued toward all people without exception. Kierkegaard’s ethics of love is one step in overcoming the ethical formalism and rationalism, but and nihilism as an aspect of alienation of man from God, other people and man’s self.